KINEMATIC ANALYSIS OF A CAM MECHANISM WITH ELASTIC ELEMENTS OF THE MECHANISM WITH ELASTIC ELEMENTS OF PAIRED CAMS OF A BOEL MECHANISM OF A WEAVING LOOM - Khudаyberdiyeva, Makhliyo; Djurayev , Аnvar; Urmanov , Nurmat (Scientific and Technical Journal of Namangan Institute of Engineering and Technology, 2024)
The article provides a diagram and principles of operation of the crank mechanism with composite cams. The results of the kinematic analysis of the mechanism with compound cams are presented, taking into account the maximum deformations of the elastic elements of the composite cams of the cam mechanism of the weaving loom. Analytical expressions describing the laws of motion of the connecting rod and rocker arm of a replacement linkage-joint mechanism with their four-link length changing are given. The kinematic characteristics of the crank mechanism with composite cams have been analyzed, and the main parameters of the system have been substantiated.